Demographic Trends and Transition in Odisha: Emerging Patterns and Implications - Das, Sibabrata (National Geographical Journal of India, 2022)
The Indian state of Odisha has seen remarkable demographic changes towards the end of the 20th century and the last one and a half decade of 21st century. During the same period, the state has also experienced socio economic transformations of varying degree. Demographic situation in Odisha was characterised by high birth rate and death rate in 1971. As per the National Family Health Survey (NFHS 4, 2015-16), Odisha has achieved replacement level of fertility. On the contrary, the mortality in the early years of childhood remains substantially high in spite of a declining trend. The demographic history of Odisha throws a number of surprises, one being the situation of high level of childhood mortality and low level of fertility. A perfect portrayal of demographic transition requires an investigation of the impact of demographic changes on socio-economic transformations and vice-versa. This paper examines the trends and regional heterogeneities in demographic scenario in the state by using the data from the Census of India, the Sample Registration System (SRS) and the National Family Health Surveys (NFHS).